Job satisfaction among executives at Syarikat Bekalan Air Selangor Sdn Bhd (SYABAS), based on Herzberg’s motivation-hygiene theory - Masrubiah, Mohd Zuki (2013)
The main purpose of this study is to examine and gain a better understanding of the significant relationships between the Herzberg’s motivation-hygiene factors towards job satisfaction among executives at SYABAS. Within these two main factors there are 11 dimension factors that researcher need to find out which one from the factor give most high impact towards job satisfaction. The dimension are listed was, motivator factors under the job content (achievement, advancement, work itself, recognition and growth). Second was, hygiene factors (company policy, relationship with peers, working security, relationship with supervisors, money and working condition). In this study convenience sampling was use to select executive from SYABAS Kuala Lumpur and Petaling Jaya, and researcher target the population was 150 employees. Questionnaires have been used to obtain the data. Data which was gathered through questionnaires was analyzed by using statistical package for social science (SPSS) software 20. Researcher has conducted reliability, Pearson correlation and Regression analysis. The results show that hygiene factors were the dominant motivators among employee job satisfaction which is the dimension of relationship with the supervisor H9 are the leading factors in this study found by the researcher, hence show that hygiene factors are accepted From eleven hypotheses developed, only eight hypotheses was accepted. There are three dimensions that have negative relationship between recognition, company policy and work security towards job satisfaction among executive at SYABAS, researcher need to reject the hypothesis H4 H6 and H8. This study also is to suggest the management of the organization to review back needs and requirements of employees in the organization of SYABAS.